2005
DOI: 10.1002/ejoc.200400575
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Charged Porphyrins by Charged and Metal‐Chelated EDTA‐Tethered β‐Cyclodextrin Dimers: A Thermodynamic Study on the Influence of Tether Charge and Flexibility on Binding Affinity

Abstract: Keywords: Cyclodextrins / Molecular recognition / Host-guest systems / PorphyrinoidsComplex formation between charged porphyrin guests and charged or neutral β-cyclodextrin (CD) host dimers linked by ethylenediamine-N,N,NЈ,NЈ-tetraacetate (EDTA) tethers was assessed by microcalorimetry. Two EDTA-tethered CD dimers (1 and 2) were employed to obtain a series of structurally similar CD dimers with different tether charges and flexibilities through either (partial) protonation or metal chelation (with Ca II or Eu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
4
0
6
Order By: Relevance
“…The formation of inclusion complexes involving 2 and the modified CyDs was possible, with the substitution of the hydroxyl groups by methyl or hydroxypropyl groups giving the b-CyD a higher flexibility. [31,32] This substitution also increases the solubility of CyDs in aqueous medium due to the breaking of the internal rigidity attributed normally to b-CyD in view of the formation of intramolecular hydrogen bonding. [33,34] As expected, the diminution in the preorganization of the b-CyD by structural modification makes difficult a tight and space-filling accommodation of dye 2, so that its mobility within the cavity is higher, reducing substantially its binding to the substrate.…”
mentioning
confidence: 97%
“…The formation of inclusion complexes involving 2 and the modified CyDs was possible, with the substitution of the hydroxyl groups by methyl or hydroxypropyl groups giving the b-CyD a higher flexibility. [31,32] This substitution also increases the solubility of CyDs in aqueous medium due to the breaking of the internal rigidity attributed normally to b-CyD in view of the formation of intramolecular hydrogen bonding. [33,34] As expected, the diminution in the preorganization of the b-CyD by structural modification makes difficult a tight and space-filling accommodation of dye 2, so that its mobility within the cavity is higher, reducing substantially its binding to the substrate.…”
mentioning
confidence: 97%
“…51 It was observed that 2 forms with the dimer (3) the 1:2 complex, i.e. 51 It was observed that 2 forms with the dimer (3) the 1:2 complex, i.e.…”
Section: Inclusion Complexes Of Cyclodextrinsmentioning
confidence: 99%
“…[14,15] In addition to the cooperative binding through which the two adjacent CD cavities of these bridged bis(CD)s can encapsulate guest molecules, the linker can contribute to the stabilization of such complexes by providing additional binding interactions or contributing to extending the overall binding site. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Secondary-face-linked β-CD dimers often show higher complexing constants than those bridged by primary faces, [18][19][20][21]35] probably due to the fact that guest Scheme 1. CD units can be linked through their primary faces, i.e., 6-6Ј bis(CD), through a head-to-tail fashion, i.e., 6-2Ј or 6-3Ј bis(CD), and through their secondary faces, i.e., 2-2Ј or 3-3Ј bis(CD).…”
Section: Introductionmentioning
confidence: 99%